Shoaling of abyssal ventilation in the Eastern Indian Sector of the Southern Ocean - Keishi Shimada; Yujiro Kitade; Shigeru Aoki; Kohei Mizobata; Lingqiao Cheng; Kunio T. Takahashi; Ryosuke Makabe; Jota Kanda; Tsuneo Odate (Communications Earth & Environment, 2022)
Under rapid and persistent freshening in source waters, a decline in the supply of Antarctic Bottom Water to the Australian-Antarctic Basin is compensated by an increase in ventilation of the layer immediately above, suggests an analysis of in situ observations since 1995.